THE ROLE OF LOCAL INSTITUTION IN DECENTRALIZED REGIONAL PLANNING (CASE STUDY: NAGARI PLANNING-BASED IN TANAH DATAR DISTRICT WEST SUMATRA PROVINCE) - NOER , MELINDA
Although the "development from below" paradigm has generated local-based development concepts, it has still worked with the general institutional forms and measured its success by a limited number of indicators which is physical and economic. In facts, there is a local institution and human social needs which cannot be measured in physical (material) and economic terms. Territorial regional planning strategy has not accommodated the social (social relation) and political dimension of the local culture into a decision making process. Regional resource allocation has been planned within economic principles (market rationality) and state law, while those resources in some regions are communal ownership which is social in nature (social rationality) as the cultural heritage. These conditions have accumulated and turned into development problems. It reveals an inadequacy of existing regional planning in the realization of "development from below" conception. This research is designed to fill in the gap of regional planning theories by introducing a local institution which is developed from below, as a basis of decision making. Decentralization has delegated some authorities to the region and local government to involve local cultural resources as a basis of the regional planning decision making process. This potential culture has already generated from below, locally and territorially organized, and traditionally related to the social and political dimensions since it is closely attached to history of the region. Local institution as such also has a specific organization and regulation in order to control the regional resources. However, the problem is the local and state regulations meet contradictives in some areas. So the question is how far the local-informal institution can play an important role in a decentralized regional planning which is formally governed? In relation to that problem, this research is focused in West Sumatra Province which meets some conditions, as follows: this province possess the local government and planning system which is based on Minangkabau-customary (adat) law, called nagari (desa level); nagari is defined as a region of unity in a community adat law as well as governmental institution at the lowest level; West Sumatra Provincial government has internalized nagari into regional policies and regulations as legal-formal-based regional planning and development; Minang ethnic groups is the fourth largest ethnic groups in Indonesia (after Java, Madura, and Sunda); and this ethnic group is well-known in preserving the adat and Minangkabau culture since the pre-colonial era. In general, the objective of this research is to investigate how far the local institution plays an important role in a decentralized regional planning. Specifically, this research aims at identifying the elements of local institution, explaining why and how the local institution play an important role in a decentralized regional planning, and explaining the improvement in regional planning and its factors. The research uses the interpretative qualitative approach. Four case studied-nagari were elected purposively, namely Nagari Pariangan, Singgalang, III Koto, and Minangkabau, within four different sub-districts in Tanah Datar District-West Sumatera Province. Qualitative and quantitative data were collected using informal-semi structured interview with open-ended questions. In-depth interview was used to gain specific and detail informations. Data analysis was done using content analysis, coding, which in turn comprehended, interpreted, and finally reported in qualitative descriptions. These findings reveal that local institution (specifically adat institution) plays an important role in decision making within decentralized regional planning. Adat institution can play such role because its social ties in the forms of social relation within organic institution, is generated from below which is based on meaning and history of the region itself. That role is played through social and political in informal and tacit social learning and democratic political process. It is found that involvement of local institution as regional social resources in regional development planning contribute to attain social and political development beside economic aims. This finding was supported by the theory that local institution is an organic institution which always lives and grows within community because it has generated from below and attached to region's history itself. As social resources, together with human, land, and economic resources, local cultural based regional planning brings about participation as the regional planning improvement. Beside that, there are also some indication improvements in social and economic returns, competitive advantage, and sustainability. This research has contributed to the knowledge enrichment in case: (1) develop the understanding of local cultural based regional planning conception; (2) enrich the communicative planning theory in explaining how traditional cultural values can be used within decision making process to improve regional planning; (3) enrich the communicative planning theory in explaining a complex characteristics of decentralized planning; (4) give some substantive and procedural inputs for decision makers in explaining changes in knowledge, understanding, attitude, and behavior of regional planning stakeholders; (5) and contribute the understanding to other regions in Indonesia and developing countries as well as finding out the appropriate local based regional planning strategy.